2009
DOI: 10.1007/s10295-008-0516-5
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel fibrinolytic protease from Fusarium sp. CPCC 480097

Abstract: A novel fibrinolytic enzyme from Fusarium sp. CPCC 480097, named Fu-P, was purified to electrophoretic homogeneity using ammonium sulfate precipitation and ion exchange and gel filtration chromatography. Fu-P, a single protein had a molecular weight of 28 kDa, which was determined by SDS-PAGE and gel filtration chromatography. The isoelectric point of Fu-P determined by isoelectric focusing electrophoresis (IEF) was 8.1, and the optimum temperature and pH value were 45 degrees C and 8.5, respectively. Fu-P cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 46 publications
3
51
1
Order By: Relevance
“…CPCC 480097 from the stems of chrysanthemums. 166 Several direct acting fibrinolytic enzymes have also been isolated from the genus Bacillus including Subtilisin DJ-4 (Bacillus amyloliquefacien), subtilisin DFE (B. amyloliquefacines) and subtilisin CK (Bacillus sp strain CK-11-4). 23 Serrapeptase (SP), a proteolytic enzyme produced by Serratia sp.…”
Section: Direct Thrombolytic Agentsmentioning
confidence: 99%
“…CPCC 480097 from the stems of chrysanthemums. 166 Several direct acting fibrinolytic enzymes have also been isolated from the genus Bacillus including Subtilisin DJ-4 (Bacillus amyloliquefacien), subtilisin DFE (B. amyloliquefacines) and subtilisin CK (Bacillus sp strain CK-11-4). 23 Serrapeptase (SP), a proteolytic enzyme produced by Serratia sp.…”
Section: Direct Thrombolytic Agentsmentioning
confidence: 99%
“…Subsequently, 20 ml of the enzyme was dispensed into 5 mm wells previously made with sterile cork borer. Plates were incubated at 37 C for 24 h. After incubation, the dimension of the clear zone was measured and number of units was determined against a calibration curve of plasmin (from human plasma, Calbiochem, Darmstadt, Germany) 9,22 .…”
Section: Fibrinolytic Activity Of Xylarinasementioning
confidence: 99%
“…Only a few endophytic fungi such as Clonostachys sp., Cladosporium sp., Fusarium strain CPCC 480097, Fusarium sp. BLB and Verticillium sp., have been reported to possess fibrinolytic activity [20][21][22] . Hence, endophytic fungi stand as an unexplored bioresource of fibrinolytic agents that can play an important role in thrombolytic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme was similar to the fibrinolytic enzyme from Fusarium sp. CPCC 480097 (Wu et al, 2009) and A. mellea metalloprotease (AMMP), a fibrinolytic enzyme from cultured mycelia of A. mellea (Wu et al, 2009), which are known to be a chymotrypsin-like serine metalloprotease and chymotrypsin-like metalloprotease, respectively.…”
Section: Effects Of Inhibitors and Metal Ions On Enzyme Activitymentioning
confidence: 99%
“…The addition of the enzyme caused a clear hollow on the plasminogen-free plate, while the size of the clear hollow did not change obviously in the presence of plasminogen, suggesting that the purified enzyme was a plasmin-like, direct-acting, fibrinolytic protease that did not require endogenous fibrinolytic factors to lyse the thrombi. Hence, secondary effects, such as platelet activation related plasmin formation caused by plasminogen activators, could be avoided (Wu et al, 2009). The degradation pattern of fibrin by the purified enzyme showed that the enzyme preferentially hydrolyzed the α chain of fibrin, followed by the β chain, and finally the γ-γ chain, with a pattern similar to those of the enzymes from C. militaris and Armillaria mellea (Lee et al, 2005).…”
Section: Hydrolysis Of Fibrinogen By the Purified Enzymementioning
confidence: 99%